Irony, Names and Linguistic Resistance: NoViolet Bulawayo’s We Need New Names as a World-Making Narrative (Altre Modernità, 2022)
Contemporary works of African literature often engage in the depiction of a geographical and cultural dislocation inscribed in today’s pattern of global migration. NoViolet Bulawayo’s We Need New Names (2013) fits within this framework as a female coming-of-age novel that follows the story of Darling, from the character’s childhood in post-2000 Zimbabwe to the alienating experience of life as a migrant in the United States of America. The peculiarity of the novel lays in Bulawayo’s linguistic choices, in particular the use of irony and the practice of (re)naming, which come to represent the feelings of un-belonging and political disillusionment that define the characters’ geo-cultural displacement. Using the normative theory of literature (Cheah 2016) as a theoretical framework, this paper further analyses the use of such literary devices as tools through which the narrative opens up to alternative worlds of representation. In this sense, this paper argues that Bulawayo’s We Need New Names can be considered as a world-making narrative of cultural and linguistic resistance against the disruption of Zimbabwe’s socio-political situation.